The influence of glutathione S-transferases M1 and M3 on the development of bladder cancer - Klaus Golka; Tobias Schmidt; Hermann M. Bolt; Silvia Selinski (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2006)
Problem: Cigarette smoking is the most important risk factor of transitional cell carcinoma of the urinary bladder. The effect of the glutathione S- transferases M1 (GSTM1) and M3 (GSTM3) on the influence of this risk factor was investigated. Methods: A total of 293 bladder cancer patients from Dortmund and Wittenberg as well as 176 surgical patients without any malignancy from Dortmund were genotyped for GSTM1 und GSTM3 according to standard PCR/RFLP methods. Smoking habits were also qualified by a standardized interview. Results: The percentage of GSTM1 negative cases was 63 % in the entire bladder cancer patient group compared to 50 % in the control group. GSTM3*A/*A genotype was 76 % in the entire group of bladder cancer cases and 74 % in controls. Smokers and ex-smokers were overrepresented in the bladder cancer patient group. A significant association between smoking status and GSTM1 or GSTM3 genotype could not be revealed. Conclusion: The elevated percentage of GSTM1 negative bladder cancer cases shows the important effect of this polymorphic enzyme on the development of bladder cancer. In contrast to some other studies, an influence of GSTM1 on the risk due to cigarette smoking could not be observed.
Keywords: 519; Bladder cancer; glutathione S-transferase M1; glutathione S-transferase M3; smoking